Efficacy of some biorational insecticides against the cactus scale pest Diaspis echinocacti (Bouché, 1833) (Hemiptera: Diaspididae) in Morocco - Mohamed El-Aalaoui; Mohamed Sbaghi (African and Mediterranean Agricultural Journal - Al Awamia, 2023)
Diaspis echinocacti (Bouché) is a significant pest affecting various cactus pear species worldwide. Over the past three years, this scale insect was able to build up a considerable population and had now reached a pest status in Morocco. To control this pest, insecticides with different modes of action were evaluated in laboratory and greenhouse. In laboratory bioassays, d-limonene at 30-150 cc/hl, mineral oil at 700-2400 cc/hl, potassium salts of fatty acid at 15-60 cc/hl, and pyriproxyfen at 8-37 cc/hl were evaluated against first instar nymphs and adult females of the cochineal, while only d-limonene applied at 150 cc/hl, mineral oil applied at 2000 and 2400 cc/hl, and potassium salts of fatty acid applied at 60 cc/hl were used in greenhouse tests. In laboratory tests, mineral oil at 2400 cc/hl, d-limonene at 150 cc/hl, and potassium salts of fatty acid at 60 cc/hl were the most effective against nymphs and adult females of the cochineal 48 hours after exposure to insecticide treatments, resulting in LT50 values of 24, 24 and 48 h (nymphs), and 48 h (adult females), respectively. Under greenhouse conditions, mineral oil at 2400 cc/hl and d-limonene at 150 cc/hl showed significantly higher mortality rates [70 and 67% (nymph) and 45 and 42% mortality (adult female), respectively] and a high potential for degrading waxy carapace covering the body of the cochineal. Effective control of this harmful pest depends on a justified use of these two insecticides (mineral oil and d-limonene) and requires the development of an integrated management approach.